THE SERVQUAL METHOD AS AN INSTRUMENT FOR THE MEASUREMENT OF HOTEL SERVICES QUALITY - Górnik, Katarzyna; Świdroń, Magdalena (Acta Scientiarum Polonorum. Oeconomia, 2010)
An increase of competition in a hotel sector is to continuous supervision and adaptation to changing market conditions. A necessary is an aspiration to total quality in purpose of satisfaction of needs and expectations of clients. The aim of study was to demonstrate the importance of various factors in development of quality, the role of service quality in the effective management of the hotel. The study was carried out with a questionnaire. The SERVQUAL method was proposed as an instrument for the measurement of perceived service quality. The degree of fulfillment of customer expectations and perceptions of three star hotel services in Szczecin was evaluated. According to calculations customers’ expectations positively exceeded the standard breakfast (0.73) and the hotel’s staff service. The study proved the importance of: communication, propriety and efforts to maintain regular guests. Negative gaps in the availability of a communication facility (-0.56) and the sense of security (-0.25) were reported. Total score obtained by SERVQUAL method was 0.14, which refl ected a high standard and quality of services. This result was close to total quality, however, the hotel had yet to work on it.